If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 2) = 4b + -10 Reorder the terms: 3(2 + b) = 4b + -10 (2 * 3 + b * 3) = 4b + -10 (6 + 3b) = 4b + -10 Reorder the terms: 6 + 3b = -10 + 4b Solving 6 + 3b = -10 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 6 + 3b + -4b = -10 + 4b + -4b Combine like terms: 3b + -4b = -1b 6 + -1b = -10 + 4b + -4b Combine like terms: 4b + -4b = 0 6 + -1b = -10 + 0 6 + -1b = -10 Add '-6' to each side of the equation. 6 + -6 + -1b = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -1b = -10 + -6 -1b = -10 + -6 Combine like terms: -10 + -6 = -16 -1b = -16 Divide each side by '-1'. b = 16 Simplifying b = 16
| 10+3[x+2]=31 | | -5x+6=3x-9 | | log(12x+2)=log(2x-1)+1 | | 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 | | -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 | | 8x-24y=144 | | 0.5r+5.2=2.8 |